Formulation and optimization of upadacitinib-loaded transdermal patches for rheumatoid arthritis with zero-order release kinetics - Talole, Shubham; Godge, Rahul; Tambe, Nikita; Mhase, Nikita (Journal of Applied Pharmaceutical Research, 2025)
Background: To develop and optimize Upadacitinib-loaded transdermal patches for rheumatoid arthritis treatment with improved patient compliance and sustained drug delivery. Methodology: Upadacitinib transdermal patches were formulated using a 3² factorial design approach with PVP K30 and HPMC K4M as key polymeric components. The patches were characterized for physicochemical, mechanical, and ex vivo permeation properties. Results and Discussion: The optimized formulation (SF8) exhibited excellent physicochemical characteristics, including high drug content (99.05 ± 0.83%), optimal mechanical properties with tensile strength of 0.912 kg/mm² and adhesion strength of 3.94 N. The ex vivo permeation reached 86.35% at 12h, with the flux of 102.91 μg/cm²/h following zero-order kinetics (R² = 0.9777). The experimental values closely matched predicted values with less than 2% error. Accelerated stability studies confirmed minimal changes in critical parameters over six months. Conclusion: The optimized Upadacitinib transdermal patch provides sustained drug delivery with zero-order release kinetics and excellent stability. This transdermal delivery system offers a promising alternative to oral therapy with potential advantages of improved patient compliance, reduced dosing frequency, and avoidance of first-pass metabolism for rheumatoid arthritis management